Effects of Curcumin Nanoparticles on Tumor Markers in Male Rats - younis, Mohammed abdulhameed (American Journal of Biomedicine and Pharmacy, 2025)
Turmeric’s active chemical, curcumin, has been shown to have potential as a cancer treatment. Bioavailability and solubility are obstacles however. Nanotechnology is a process that has produced nanocurcumin and this can remove these restrictions. It can potentially be used for cancer treatment. A study was conducted to evaluate the efficacy of curcumin nanoparticles in lowering the levels of tumor markers in male rats. We compared the action of curcumin nanoparticles with the standard curcumin-treated and untreated tumor-induced groups. Rats given the nanoparticles had better treatment effects because their levels of markers for cancer (alpha-fetoprotein (AFP), carcinoembryonic antigen (CEA), and CA-19-9) were markedly lower.